WORLD-RENOWNED HORTICULTURAL SCIENTISTS IN THE HISTORY OF UMAN NATIONAL UNIVERSITY OF HORTICULTURE (end of the XIXth –first half of the XXth century) - Нижник, Світлана; Соловей, Галина (SWorldJournal, 2024)
The article is devoted to the analysis of the scientific and practical activities of outstanding personalities of the Uman National University of Horticulture and their influence on the development of horticulture in Ukraine. Based on the complex use of g